EFFECT OF EXCISE RATES, PER CAPITA INCOME, AND EDUCATION LEVEL ON NON-CHILD SMOKER RATES - Rifki Rahmazaki Adam; Aditya S. Purwana (Kesatuan Press, 2022)
According to research by Tobacco Atlas in 2015, Indonesia has the third largest number of smokers in the world after China and India, with an estimated number of smokers at around 53.7 million. Smoking is a habit that harms health. Smoking causes heart disease, lung, oral, stomach, skin, and other conditions. This study aims to empirically examine the relationship between the excise rate, per capita income, and education level on the level of non-child group smokers in Indonesia for the 2015-2020 period. This period was chosen following Presidential Decree No. 28 of 2008 and Permenperin No.117/M- IND/PER/10/2009, which discusses the Tobacco Products Industry (IHT) roadmap and states that from 2015 to 2020, the priority is on the health aspect. This research was conducted with a quantitative approach using the panel data regression method. The results of this study conclude that the independent variables in this study simultaneously affect the dependent variable. In addition, it is known that the variable excise tax rate and education level partially have a significant effect on the dependent variable with a positive coefficient. In contrast, the income per capita variable partially has a substantial impact on the dependent variable with a negative coefficient.